Comparison of risk indicators of dental caries in children with and without cleft lip and palate deformities - Rubina Shashni; Ashima Goyal; Krishan Gauba; Ashok Kumar Utreja; Pallab Ray; Ashok Kumar Jena (Wolters Kluwer Medknow Publications, 2015)
Objective: To test the hypothesis that there are no differences in various risk factors of dental caries among children with cleft lip and palate when compared to non-cleft high caries risk and non-cleft caries free children. Design: Seventy-three children in the age range of 4-9 years comprised three groups; Group-I (n = 23, children with cleft lip and palate), Group-II (n = 25, non-cleft high caries risk children) and Group-III (n = 25, non-cleft caries free children). Various risk factors for dental caries like type of oral hygiene practice, sugar exposures/day, developmental defects of enamel, caries activity, salivary streptococci mutans levels and lactobacilli levels were evaluated and compared among the three groups of children. Results: The mean deft score among Group-II children was significantly more (P < 0.01) as compared to the Group-I children. The mean deft + DMFT score among Group-I and Group-II children was comparable (P = 0.149). Developmental enamel defects were more among Group-I children as compared to Group-II and Group-III children (P < 0.01). Hypoplasia of the maxillary anterior teeth was more common among Group-I children as compared to Group-II (P < 0.05) and Group-III children (P < 0.001). The association between hypoplastic teeth and dental caries was significant (P < 0.05). The salivary acidogenic potential as evaluated by Snyder test was comparable among Group-I and Group-II children. The salivary streptococcus mutans levels in Group-I and Group-II children were higher when compared to lactobacillus counts. Conclusion: The risk factors of dental caries among children with cleft lip and palate were more as compared to non-cleft high caries risk and non-cleft caries free children.